Effectiveness of Selected Medicinal Plants in Reducing Blood Pressure in Pregnant Women with Hypertension in Banten Province (2024) - Sonda Nur Assyaidah; Duriah; Mira Munawaroh; Muhfidoh; Nova Cahyani; Nurjanah; Millya Kristi Sahentumbage (Postgraduate, University of Mataram, 2025)
Hypertension in pregnancy is a major cause of maternal and fetal morbidity and mortality. This study aims to analyze the effectiveness of Amaranthus Caudatus, Cocos Nucifera L, Punica Granatum L, Sechium Edule, Solanum Lycopersicum, Brassica Oleracea L, Moringa Oleifera, Apium Graveolens L, Persea Americana, and Cucumis Melo L in reducing blood pressure in prehypertensive pregnant women in Banten Province. A quasi-experimental design with a pretest and posttest nonequivalent control group approach and total sampling technique was used. The results showed a significant reduction in blood pressure (p<0.05), with Punica Granatum L and Sechium Edule demonstrating a significant difference in effectiveness (p=0.000). This study confirms that non-pharmacological management can be an alternative for lowering blood pressure in prehypertensive pregnant women.